Possible production of neutron-rich Md isotopes in multinucleon transfer reactions with Cf and Es targets; Physical Review C; Vol. 99, iss. 5 - Mun Myeonghwan; Kwak Kyujin; Adamyan G. G. Gurgen Grigorjevich; Antonenko N. V. Nikolay Viktorovich (2019, 2019)
Title screen